A list of alien taxa for South Africa - Zengeya, Tsungai; Faulkner, Katelyn; Mtileni, Promise; Fernández Winzer , Laura; Kumschick, Sabrina; McCulloch-Jones, Emily; Miza-Tshangana , Siyasanga; Robinson, Tamara; Sifuba, Aviwe; Engelbrecht , Whitney; van Wilgen, Brian; Wilson, John (African Biodiversity & Conservation, 2026)
This paper presents a comprehensive list of alien taxa in South Africa developed as part of triennial national status reports on biological invasions. It includes: taxa that are, have been, or were proposed to be regulated; alien taxa that are or have been present in South Africa (including those only ever recorded in quarantine facilities); taxa that are native to a part of South Africa that have formed native-alien populations in another part of the country; and taxa which have been categorised at some point as alien or for which the risk of invasion in South Africa has been evaluated. Names used previously are included so it is clear why taxa listed in historical sources are no longer considered alien or present, and how such names have been interpreted in terms of the latest authoritative taxonomic sources. The list also includes information on the invasion status of the taxa, their pathways, distributions, impacts and management, with metadata provided for all 38 variables, including confidence and data sources for 23 of them. The development of documented and repeatable workflows ensures it is clear why taxa (and associated information) are included in the list and facilitates reviews and updates. Based on information up to the end of December 2022, the list includes over 6 000 taxa, of which over 3 500 are alien taxa confirmed as present outside of captivity or cultivation. However, several key data sources still need to be verified and integrated into the list (particularly taxa in captivity or cultivation). Thus, this list should not yet be regarded as a complete baseline of the knowledge of alien taxa present in South Africa. The list is presented in a manner that is tidy and FAIR (findable, accessible, interoperable, reusable) and will be maintained, expanded and updated, so that the list will be dynamic and aim for completeness. By so doing, the list will allow the number and status of alien taxa to be tracked over time, informing management planning and regulatory decisions.